KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN KINERJA - Indra Roza; Febri Yuliani; Kiswanto Kiswanto (Universitas Riau, 2017)
Transformational Leadership, Motivation On Performance. The purpose of this study was to identify and analyze the extent of the transformational leadership and motivation affects a performance of Civil Servants in Civil Service Agency, Education and Training of Riau Province. The sampling technique used in this study is a simple random sampling amounted to 116 as a sample. Methods of data collection through questionnaires and documentation study. Methods of data analysis using multiple linear regression using SPSS. The results showed that transformational leadership and motivation significantly influence the performance of Civil Servants. The significance influence of the of transformational leadership and motivation on the performance of Civil Servants can be shown from the value Fvalue=184,565 > Ftable=3,08, level of probability (p) = 0,000 or less than 0.05, this means that transformational leadership and motivation have a significant effect simultaneously on the performance of Civil Servants. While the t value of X1 = 0,187 < t table = 1,98 which mean that transformational leadership had no effect on the performance of Civil Servants in Civil Service Agency, Education and Training of Riau Province And t value of X2 = 11,416 < t table = 1,98 which means that motivation had partial effect on the performance of Civil Servants in Civil Service Agency, Education and Training of Riau Province.